PENGARUH SUKUK RITEL PEMERINTAH TERHADAP PENGHIMPUNAN DANA PIHAK KETIGA BANK SYARIAH - Rizal Yaya; Ekta Sofiyana (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
This research aims at investigating factors that influence third parties funds (TPF) of Indonesian Islamic banks during the issuance of government retail sukuk 2012-2015. Data are taken from quarterly statistical reports of Indonesian Islamic banking and analysed by using multiple linear regression. The results show that retail sukuk has negative influence, while offices number, company size, and return for the third parties have positive influence on TPF collected. As having negative influence, Islamic banks should anticipate future issuance of retail sukuk by improving their internal performance. Failing to anticipate it, they may suffer of decreasing amount of TPF.